Problems of formation of a profitable part of local budgets of the Republic of Kazakhstan - Igenbaev, E. Zh. (Journal of Economic Research & Business Administration, 2015)
In this article I tried to give the main directions of improvement of formation of revenues of local budgets for a sustainable development of the region. Fruitful performance of function of the state requires creation of the corresponding control system by public finances. The most important problem of management of state revenues – to promote sustainable and effective economic development of the country by optimization of formation of revenues of the State budget of thecountry, generally by means of taxation and rational planning of the public expenditures. At definition of the priority directions of improvement of formation of revenues of local budgets for a sustainable development of the region, it is possible to allocate the following ways:1) development of base of own income of local budgets, as bases of financial independence of the region and economic development;2) development of system of the interbudgetary support of regions of the Republic of Kazakhstan 3) granting to local budgets of the expanded rights of loan of means in the internal and external markets.